AÃ‡ÃƒO DO ÃCIDO 2, CLOROETILFOSFÃ”NICO NA MATURAÃ‡ÃƒO DA UVA â€œNIÃGARA ROSADAâ€ - Sampaio, S. Vladimir Rodrigues; DemÃ©trio, Clarice Garcia B. (REVISTA DE AGRICULTURA, 2020)
AÃ‡ÃƒO DO ÃCIDO 2, CLOROETILFOSFÃ”NICO NA MATURAÃ‡ÃƒO DA UVA â€œNIÃGARA ROSADAâ€